Local field potentials reflect dopaminergic and non-dopaminergic activities within the primate midbrain - Pasquereau, Benjamin (Neuroscience, 2018)
Midbrain dopamine neurons are thought to play a crucial role in motivating behaviors toward desired goals. While the activity of dopamine single-units is known to adhere closely to the reward prediction error signal hypothesized by learning theory, much less is known about the dynamic coordination of population-level neuronal activities in the midbrain. Local field potentials (LFPs) are thought to reflect the changes in membrane potential synchronized across a population of neurons nearby a recording electrode. These changes involve complex combinations of local spiking activity with synaptic processing that are difficult to interpret. Here we sampled LFPs from the substantia nigra pars compacta of behaving monkeys to determine if local population-level synchrony encodes specific aspects of a reward/effort instrumental task and whether dopamine single-units participate in that signal. We found that reward-correlated information is encoded in a low-frequency signal (<32-Hz; delta and beta bands) that is synchronized across a neural population that includes dopamine neurons. Conversely, high frequency power (>33-Hz; gamma band) was anticorrelated with predicted reward value and dopamine single-units were never phase-locked to those frequencies. This high-frequency signal may reflect inhibitory processes that were not otherwise observable. LFP encoding of movement-related parameters was negligible. Together, LFPs provide novel insights into the multidimensional processing of reward information subserved by dopaminergic and other components of the midbrain.